THERMAL ANALISYS FOR A DOUBLE SIDED LINEAR INDUCTION MOTOR - Costica Nituca (European Scientific Journal, ESJ, 2013)
The paper presents an analysis of the thermal regime for a double sided linear induction motor with ring windings and plate armature. The motor can operate in an oscillating drive system with fast response and low distance movement or for small and medium movement application. A thermal model is realized for the linear induction motor and it is compared with experimental data regarding the thermal aspects.